Requirements for Transmission, Steering Gears Control And Suspension of the Carher for Hot Climate Conditions (Texas Journal of Engineering and Technology, 2022)
Preparation of transmission mechanisms of vehicles intended for operation in sandy-desert terrain provides for cleaning mechanisms from dust and dirt, checking the serviceability of all mechanisms and adjusting them in accordance with the instructions of manufacturers' instructions, cleaning external parts and crankcases of mechanisms from accumulations of contaminants and used oils and lubricants. Particular attention should be paid to cleaning the spline joints of the cardan shafts and filling them with fresh lubricant.